EMBEDDING ADVANCE CARE PLANNING (ACP) BEST PRACTICES IN LONG TERM CARE FACILITIES (LTC): GIVING ACP ITS BEST CHANCE. Issue 2 (1st June 2013) - Iversen, S; Berg, B; Simon, J
Abstract : Background: LTC residents frequently have cognitive impairment, are at risk of intercurrent illnesses and being unable to express their preferences when medical decisions need to be made. Consequently, ACP in LTC often requires staff and family participating with/on behalf of the resident making advance decisions about intent of care and use of hospital services should a sudden deterioration arise. It is not known how best to embed such ACP in the fabric of LTC delivery. Aim: To use an Inquiry to Action project, including patient/family survey, to describe the strengths and challenges of ACP in LTC and inform best practices for embedding ACP in LTC Methods: Using a quality improvement initiative 'Inquiry to Action' akin to the qualitative Action Research, a nurse educator sought to understand how ACP occurs in three urban LTC and to develop a plan of action to improve the quality and frequency of LTC ACP communication. In addition we adapted and piloted a validated survey from acute care (ACCEPT), to collect perspectives on ACP of residents and their family. Results: The commitment to ACP from facility leaders and staff varied with local context. We will describe facility strategies and work flow processes that family, residents and staff reported as facilitative or challenging to ACP. Conclusion: An implementation framework, adaptable to local context, was created of best practice suggestions related to organisational and business processes, resident and family member engagement, ongoing staff education and continuous quality improvement.